2022
DOI: 10.1007/s40744-022-00515-z
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Etanercept Biosimilar SB4 for Rheumatic Diseases in South Korea: Real-World Post-marketing Surveillance Data

Abstract: Introduction: SB4 is the first approved biosimilar of etanercept, a biologic tumor necrosis factor inhibitor, to treat various autoimmune diseases including axial spondylarthritis (axSpA), rheumatoid arthritis (RA), psoriatic arthritis (PsA), and plaque psoriasis (PsO). This post-marketing surveillance (PMS) study of SB4 investigated safety and effectiveness in routine clinical practice and is part of the drug approval process in Korea. Methods: This prospective, multi-center, openlabel, observational, phase I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Several observational studies assessed the effectiveness of biosimilar products in these remaining indications and showed that there was no difference between originator and biosimilar products. However, they were often small, 4 5 non-comparative [6][7][8] or pathology-specific, [9][10][11][12] as we already did for inflammatory bowel diseases using the same database from 2015 to 2017. 13 14 In Europe, four IFX, four ETA and 12 ADA biosimilars have been approved from 2015, 2016 and 2018, respectively, 15 based on bioequivalence data demonstrated in 1-3 indications.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Several observational studies assessed the effectiveness of biosimilar products in these remaining indications and showed that there was no difference between originator and biosimilar products. However, they were often small, 4 5 non-comparative [6][7][8] or pathology-specific, [9][10][11][12] as we already did for inflammatory bowel diseases using the same database from 2015 to 2017. 13 14 In Europe, four IFX, four ETA and 12 ADA biosimilars have been approved from 2015, 2016 and 2018, respectively, 15 based on bioequivalence data demonstrated in 1-3 indications.…”
Section: What This Study Addsmentioning
confidence: 99%